2023
DOI: 10.1039/d2nr06096e
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed Mn atoms coordinated with N and O within an N-doped porous carbon framework for boosted oxygen reduction catalysis

Abstract: Developing efficient and robust catalysts to replace Pt group metals for oxygen reduction reaction (ORR) is conducive to achieve highly efficient energy conversion. Here, we develop a general ion exchange...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
(64 reference statements)
0
31
0
Order By: Relevance
“…[33] The chemical states of the as-prepared samples were further studied by X-ray photoelectron spectroscopic (XPS). The high-resolution XPS spectra of N 1s for Fe1/NSOC and Fe1/NC (Figure S7a) exhibit similar peak positions and intensities, suggesting the existence of pyridinic N/FeÀ N, pyrrolic N and graphitic N. [26,34] The presence of FeÀ N indicates the Fe single atoms coordinated with the surrounding N atoms in both catalysts. The high-resolution O 1s XPS spectra in Figure 2a show the peaks for three oxygen Angewandte Chemie components, including ketonic oxygen (C=O, O1, � 531.2 eV), oxygen atoms in epoxy (CÀ OÀ C) or hydroxyl groups and carbonyl oxygen in ester groups (O2, � 532.0 eV), and the epoxy oxygen in ester groups (O3, � 533.2 eV).…”
Section: Resultsmentioning
confidence: 91%
“…[33] The chemical states of the as-prepared samples were further studied by X-ray photoelectron spectroscopic (XPS). The high-resolution XPS spectra of N 1s for Fe1/NSOC and Fe1/NC (Figure S7a) exhibit similar peak positions and intensities, suggesting the existence of pyridinic N/FeÀ N, pyrrolic N and graphitic N. [26,34] The presence of FeÀ N indicates the Fe single atoms coordinated with the surrounding N atoms in both catalysts. The high-resolution O 1s XPS spectra in Figure 2a show the peaks for three oxygen Angewandte Chemie components, including ketonic oxygen (C=O, O1, � 531.2 eV), oxygen atoms in epoxy (CÀ OÀ C) or hydroxyl groups and carbonyl oxygen in ester groups (O2, � 532.0 eV), and the epoxy oxygen in ester groups (O3, � 533.2 eV).…”
Section: Resultsmentioning
confidence: 91%
“…[33] The chemical states of the as-prepared samples were further studied by X-ray photoelectron spectroscopic (XPS). The high-resolution XPS spectra of N 1s for Fe1/NSOC and Fe1/NC (Figure S7a) exhibit similar peak positions and intensities, suggesting the existence of pyridinic N/FeÀ N, pyrrolic N and graphitic N. [26,34] The presence of FeÀ N indicates the Fe single atoms coordinated with the surrounding N atoms in both catalysts. The high-resolution O 1s XPS spectra in Figure 2a show the peaks for three oxygen components, including ketonic oxygen (C=O, O1, � 531.2 eV), oxygen atoms in epoxy (CÀ OÀ C) or hydroxyl groups and carbonyl oxygen in ester groups (O2, � 532.0 eV), and the epoxy oxygen in ester groups (O3, � 533.2 eV).…”
Section: Resultsmentioning
confidence: 91%
“…[24,25] Recently, it has been also demonstrated that the oxygen groups, such as the epoxy group, near the atomically dispersed metal centers play a significant role in determining the selectivity and catalytic activity during ORR process. [26][27][28] Except for the modification effect, these nonmetal atoms (e.g., C and N atoms) in SACs can also participate in the electrocatalysis process as additional active sites, which offers a promising strategy to further boost the catalytic activity. [29] However, in-depth understanding the roles of these heteroatoms in SACs is still missing, and a systematic investigation is of great significance to investigate the catalytic mechanism at the atomic level, which will guide the design of efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations are a useful approach to investigate the thermodynamics of intermediates over electrocatalysts and have been applied to explore the reaction mechanism of the acidic OER. [140][141][142][143][144][145] However, the reaction mechanism of DFT may not be accurate because OER steps in different reaction mechanisms can exhibit sample η. Moreover, the surfaces of electrocatalysts usually undergo reconstruction during the OER in acid solutions, so real active materials should be the obtained species after structural evolution.…”
Section: Discussionmentioning
confidence: 99%